PENDAMPINGAN PENGGUNAAN MEDIA PROMOSI INSTAGRAM PADA USAHA KONVEKSI - Mariskha, Mariskha; Alhadi, Esya; Pebriyanti, Yulia (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
Mrs. Amin's convection business was founded in 2003 or around 20 years. Based on age, this convection business is considered well established. However, in reality, this business has not experienced significant changes, starting from income ranging from IDR 2,000,000-IDR 3,000,000 per month, even since Covid-19 has experienced a decline, the business premises are still rented, and the promotional methods used are still strictly conventional. Therefore, employees who work to help convection businesses often do not come in and even quit. In fact, many customers are satisfied with the results of this convection production on the grounds that the product is comfortable to use and meets their expectations. The problem is that even with increasingly sophisticated technological changes, this business does not utilize technology in promotion and still uses word of mouth promotion. One of the social media that is often and easily used by business people to promote products, both goods and services, is the social media Instagram. The implementation method used is to create promotional designs through Instagram media and provide assistance in using Instagram social media as a promotional tool.